2022
DOI: 10.1097/scs.0000000000008856
|View full text |Cite
|
Sign up to set email alerts
|

Application of Skin-stretching Device for Closing Scalp Defect

Abstract: Background: The scalp defect was a clinical common constructive challenge. This research verified the efficacy of the skin-stretching device in the treatment of scalp defect and assessed the associated complications. Methods: The clinical data of 12 patients with scalp defect treated with skin-stretching device from January 2020 to January 2021 were collected. We used EASApprox skin-stretching device for the treatment of scalp defect. We described a detailed reconstruction procedure for this treatment. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…According to previous studies, small to moderate scalp defects (≤20 cm 2 ) can be repaired with local flap transfer, and large ones (>20 cm 2 ) can be covered with a free anterolateral femoral flap. [3,4] Additionally, clinical trials have demonstrated the efficacy of artificial dermis, [5] skin-stretching devices, [6] and tissue dilators [7] in treating scalp defects. All the aforementioned methods involve surgery and must be performed under local or general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, small to moderate scalp defects (≤20 cm 2 ) can be repaired with local flap transfer, and large ones (>20 cm 2 ) can be covered with a free anterolateral femoral flap. [3,4] Additionally, clinical trials have demonstrated the efficacy of artificial dermis, [5] skin-stretching devices, [6] and tissue dilators [7] in treating scalp defects. All the aforementioned methods involve surgery and must be performed under local or general anesthesia.…”
Section: Introductionmentioning
confidence: 99%